Kompentensi Guru Pendidikan Agama Kristen Dalam Mendesain Pembelajaran Di Era Disrupsi Teknologi - Yuliusman Laia (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
In the era of educational technology disruption, the role of general teachers including Christian religion teachers plays an important role in realizing learning in the era of technological disruption, by changing teaching strategies, methods and media. What is assisted by the development of digital technology with the support of the internet, remains effective in implementing learning effective. The problems faced are inseparable from the growth of the digitalization revolution in the field of education, where the use of information technology is a connecting factor. It is necessary to adjust pedagogical visualization. In this regard, the author uses library research techniques to find sources of material in various sources of literature, such as journal articles, books, published articles and other information on the internet. Teachers are required to have academic, intellectual, professional, ethical, and halal qualifications. As a result, Christian professional expertise in the field of Christian education also encourages him to consider himself a teacher, especially in his class. In conclusion, the era of disruption to the performance of PAK teachers is the impact of the Industrial Revolution 4.0 era. Currently is a period of upheaval that disrupts the comfort, peace, and welfare of PAK teachers in carrying out their teaching duties and responsibilities